2008
DOI: 10.1359/jbmr.080601
|View full text |Cite
|
Sign up to set email alerts
|

MEPE-ASARM Peptides Control Extracellular Matrix Mineralization by Binding to Hydroxyapatite: An Inhibition Regulated by PHEX Cleavage of ASARM

Abstract: Hyp mice having an inactivating mutation of the phosphate-regulating gene with homologies to endopeptidases on the X-chromosome (Phex) gene have bones with increased matrix extracellular phosphoglycoprotein (MEPE). An acidic, serine-and aspartic acid-rich motif (ASARM) is located in the C terminus of MEPE and other mineralized tissue matrix proteins. We studied the effects of ASARM peptides on mineralization and how PHEX and MEPE interactions contribute to X-linked hypophosphatemia (XLH). ASARM immunoreactivit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

20
212
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 178 publications
(232 citation statements)
references
References 53 publications
20
212
0
Order By: Relevance
“…However, a recent report (37) also suggests that PHEX degrades the circulating phospho-ASARM peptide, which inhibits matrix mineralization. During normal matrix mineralization in vitro, treatment of MC3T3-E1 cells with exogenous PHEX alone does not result in a significant increase in mineralization and PHEX rescues mineralization inhibition when exogenous phospho-ASARM is present (37). Collectively, we contend that when the PHEX level is greater than the MEPE level, MEPE is protected from cathepsin B cleavage action by PHEX.…”
Section: Mepe Expression Is Strongly Stimulated By Bmp-2 Treatment Anmentioning
confidence: 74%
“…However, a recent report (37) also suggests that PHEX degrades the circulating phospho-ASARM peptide, which inhibits matrix mineralization. During normal matrix mineralization in vitro, treatment of MC3T3-E1 cells with exogenous PHEX alone does not result in a significant increase in mineralization and PHEX rescues mineralization inhibition when exogenous phospho-ASARM is present (37). Collectively, we contend that when the PHEX level is greater than the MEPE level, MEPE is protected from cathepsin B cleavage action by PHEX.…”
Section: Mepe Expression Is Strongly Stimulated By Bmp-2 Treatment Anmentioning
confidence: 74%
“…(10,14,67) The ASARM region in human MEPE spans residues 508 to 525 at the C-terminal end of the protein, whereas in OPN it is found more centrally. (13,14,68) Previously, we demonstrated that PHEX is able to cleave the potent mineralization-inhibiting ASARM peptide from MEPE and OPN. (13,14) In addition, we reported on ASARM binding to hydroxyapatite mineral to provide a mechanistic explanation for how loss of PHEX activity in XLH might lead to extracellular matrix accumulation of ASARM, resulting in osteomalacia.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, previous in vivo studies have shown partial correction of the osteomalacic phenotype when Phex/PHEX is overexpressed in osteoblasts, (83,84) and local, microenvironmental effects of PHEX within the extracellular matrix have been explicitly proposed. (13,14,48) The mouse bone extracts used in this study derive from the demineralized fraction enriched in the mineral-binding peptides/proteins thought to be regulating matrix mineralization. We demonstrate by immunoblotting the accumulation of a $35-kDa OPN fragment in extracts of Hyp mouse bone that is absent in bone extracts from wild-type counterpart mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MEPE proteolysis generates the protease-resistant acidic serine aspartate rich MEPE associated motif (ASARM) peptide, which directly inwhich directly inhibits calcium oxalate crystallization and crystal growth on the extracellular matrix (Hoyer et al 2001) and promotes inhibition of the renal NPT2 phosphate co-trans- Mycobacterium leprae downregulates the expression of PHEX in Schwann cells and osteoblasts porter, affecting renal phosphate handling (Rowe et al 2004). The MEPE-derived ASARM peptide must be phosphorylated to play its role as a PHEX substrate (Addison et al 2008). It was recently demonstrated that osteopontin (OPN), a member of the small integrin-binding ligand N-linked glycoproteins family, is also a source of ASARM peptide.…”
mentioning
confidence: 99%